Differences in forearm strength, endurance, and hemodynamic kinetics between male boulderers and lead rock climbers. Issue 9 (21st October 2017) - Fryer, S.; Stone, K. J.; Sveen, J.; Dickson, T.; España-Romero, V.; Giles, D.; Baláš, J.; Stoner, L.; Draper, N.
Abstract : This study examined differences in the oxygenation kinetics and strength and endurance characteristics of boulderers and lead sport climbers. Using near infrared spectroscopy, 13-boulderers, 10-lead climbers, and 10-controls completed assessments of oxidative capacity index and muscle oxygen consumption (m⩒O2 ) in the flexor digitorum profundus (FDP), and extensor digitorum communis (EDC). Additionally, forearm strength (maximal volitional contraction MVC), endurance (force–time integral FTI at 40% MVC), and forearm volume (FAV and ΔFAV) was assessed. MVC was significantly greater in boulderers compared to lead climbers (mean difference = 9.6, 95% CI 5.2–14 kg). FDP and EDC oxidative capacity indexes were significantly greater ( p = .041 and .013, respectively) in lead climbers and boulderers compared to controls (mean difference = −1.166, 95% CI (−3.264 to 0.931 s) and mean difference = −1.120, 95% CI (−3.316 to 1.075 s), respectively) with no differences between climbing disciplines. Climbers had a significantly greater FTI compared to controls (mean difference = 2205, 95% CI= 1114–3296 and mean difference = 1716, 95% CI = 553–2880, respectively) but not between disciplines. There were no significant group differences in ΔFAV or m⩒O2 . The greater MVC in boulderers may be due to neural adaptation and not hypertrophy. A greater oxidative capacity index in both climbing groups suggests that irrespective of climbing discipline, trainers, coaches, and practitioners should consider forearm specific aerobic training to aid performance.